The Aino 2.0 model - Juha Kilponen; Seppo Orjasniemi; Antti Ripatti; Fabio Verona (Bank of Finland, 2016)
This paper presents Aino 2.0 – the dynamic stochastic general equilibrium (DSGE) model currently used at the Bank of Finland for forecasting and policy analysis. The paper provides a detailed theoretical description of the model, its estimation and how it can be used to interpret the evolution of the Finnish economy between 1995 and 2014, including the rise and fall of the electronics industry, the global financial crisis, and the stagnant growth performance since the end of the financial crisis.
URN:NBN:fi:bof-201606011162
Keywords: C11; C53; E32; E37; 330